Perancangan Aplikasi Sistem Pakar Doagnosa Awal Penyakit Batu Ginjal Berbasis Web Dengan Menggunakan Metode Forward Chaining - Mukhroji Mukhroji; Ismuhadi Ismuhadi (JURNAL ILMIAH INFORMATIKA, 2022)
Kidney is a very important organ in the human body where the kidney acts as a filter that can remove excess air, acid and salt in the body. Damage to the kidneys can be fatal to the body and one of the things that can cause damage to the kidneys is kidney stones (nephrolithiasis). In Indonesia in general and in Aceh in particular, the mortality rate of people with kidney disease continues to increase. Lack of public awareness and knowledge is one of the factors that causes the death rate to continue to increase. One way to increase awareness and increase public knowledge about kidney stone disease is the existence of an expert system application. This study builds a website-based application for an expert system for diagnosing kidney stone disease using the forward chaining method. There are 3 main points in this application, which is education about kidney stone disease, the second is an expert system for diagnosing kidney stone disease, and the third is information on hospitals, clinics and internal medicine specialists in Aceh and if possible the first information contact number. This application is built using codeigneter software and can display diagnostic results quickly and can be accessed globally because this application is online.